Effect of demulsification on anionic-stabilized oil-in-water emulsion using Graphene Oxide: article - Zukmi, Nur Arifah Nabila; Dollah, Aqilah (2018)
Emulsion problem is one of the problem in oil and gas industry that needs further attention. Although there are many method to break emulsion, and a few demulsifier had been recognized, finding the right demulsifier that gives the best outcome at low cost and high separation rate remains a problem. Graphene Oxide (GO), due to its amphiphilic behavior is recognized as one of the potential demulsifier. In this study, GO was synthesized by using modified Hummer’s method and was characterized by using XRD, FTIR and zeta sizer. Then, the effect of GO as demulsifier in breaking emulsion at different water cut was investigated by using demulsification test and result shows that different water cut will results in different trend and different optimum GO dosage. Water cut 1:2 showing increase in concentration of GO will increase the final volume of water separated. However, the best performance of GO in separating emulsion is at water cut 1:3 with over 98% separation. Also, performance of GO in different pH was further investigated. It was found out that GO can perform well in acidic condition, although in this study the result might be affected by anionic condition of emulsion. Although the performance of GO in alkali condition was not as good as in acidic condition, there are still separation occurring although the trend was rather hard to determine. To further examine the result, concentration of oil in separated waster was measured using UV Vis and result shows that oil concentration of each tests correspond to the rate of separation. Zeta potential at different pH was conducted and it was confirmed that anionic surfactant causes decrease in value of zeta potential thus explains the separation even in alkali condition.